2022
DOI: 10.1089/jpm.2021.0509
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Lemborexant for Insomnia in Cancer Patients with Delirium

Abstract: Delirium occurs very frequently in cancer patients. Insomnia is a symptom of delirium. Lemborexant is a drug that regulates sleep–wake rhythms without causing extrapyramidal symptoms. Based on its ability to improve sleep, lemborexant is expected to have efficacy for insomnia with delirium. The purpose of this study was to determine the efficacy of lemborexant for insomnia in cancer patients with delirium. A retrospective observational study was conducted between July 2020 and February 2021. Fourteen patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Although previous meta-analyses showed that suvorexant was effective in preventing delirium, 35 the present cohort study is the first to include two orexin receptor antagonists (suvorexant and lemborexant) and a melatonergic agonist (ramelteon) and examine their association with delirium prevention. Moreover, while previous studies [26][27][28][29][30][31][32][33][34][36][37][38][39][40][41]43,44 on delirium were conducted in specific population groups at a high risk of delirium, such as older adults, ICU patients, and those in postoperative periods, this study included the general population; therefore, it may be valuable in that it reflects a wider range of cases observed in clinical practice. In this study, suvorexant and lemborexant were significantly associated with a lower risk of delirium in hospitalized patients under all conditions, whereas benzodiazepines significantly increased the occurrence of delirium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous meta-analyses showed that suvorexant was effective in preventing delirium, 35 the present cohort study is the first to include two orexin receptor antagonists (suvorexant and lemborexant) and a melatonergic agonist (ramelteon) and examine their association with delirium prevention. Moreover, while previous studies [26][27][28][29][30][31][32][33][34][36][37][38][39][40][41]43,44 on delirium were conducted in specific population groups at a high risk of delirium, such as older adults, ICU patients, and those in postoperative periods, this study included the general population; therefore, it may be valuable in that it reflects a wider range of cases observed in clinical practice. In this study, suvorexant and lemborexant were significantly associated with a lower risk of delirium in hospitalized patients under all conditions, whereas benzodiazepines significantly increased the occurrence of delirium.…”
Section: Discussionmentioning
confidence: 99%
“…A new orexin receptor antagonist, lemborexant, was approved by the US Food and Drug Administration in 2019 and was subsequently approved in Japan in 2020. A pilot study on patients with cancer 43 reported sleep improvement following lemborexant usage for delirium. A retrospective observational study 44 on emergency hospitalized patients reported that lemborexant may be effective in preventing delirium.…”
mentioning
confidence: 99%
“…26,27 Suvorexant has been reported to have a preventive effect against delirium. [23][24][25] Terada et al 28 reported that lemborexant is also effective in sleep disturbances in cancer patients with delirium. However, few articles have reported the You are prohibited from making this PDF publicly available.…”
mentioning
confidence: 99%